Value distribution and the Lemma of the logarithmic derivative on polydiscs - Wilhelm Stoll (International Journal of Mathematics and Mathematical Sciences)
Value distribution is developed on polydiscs with the special emphasis that the value distribution function depend on a vector variable. A Lemma of the logarithmic derivative for meromorphic functions on polydiscs is derived. Here the Bergman boundary of the polydiscs is approached along cones of any dimension and exceptional sets for such an approach are defined.